Broadband metamaterial absorber with enhanced angular stability using characteristic mode analysis - Junfei Gao; Xiaojun Huang; Qi Xue; Lina Gao; Yutao Ma; Linyan Guo (Results in Engineering, 2025)
The integration of broadband functionality, polarization insensitivity, angular stability, and low-profile design in metamaterial (MM) absorbers remains a significant challenge. This study introduces a novel design approach utilizing characteristic mode (CM) analysis, enabling intuitive and efficient optimization of frequency-selective surfaces (FSSs) at the absorber’s top layer. Four distinct FSS configurations were developed, achieving over 90 % absorption in specific bands: 8.22 – 16.79 GHz, 8.24 – 17.90 GHz, 6.35 – 19.0 GHz, and 6.22 – 21.10 GHz. Emphasis was placed on enhancing angular stability while maintaining a compact structure. The finalized absorber exhibits an ultra-wideband response spanning 6.22 – 21.10 GHz (C, X, Ku bands), with a full-width half-maximum bandwidth of 108.9 % and a minimal thickness of 0.083 λL. Fabrication and experimental validation confirmed the design’s robustness, aligning closely with numerical simulations. This work highlights the efficacy of CM analysis in guiding MM absorber design, offering a systematic framework to address multifunctional requirements. The achieved performance combining broadband absorption, polarization insensitivity, and angular stability positions the proposed absorber as a promising solution for advanced electromagnetic applications.